The Role of Language in Thought Formation and Personality - Alejandro, Javier (International Journal of Multidisciplinary Sciences, 2024)
Language is a communication tool that plays an important role in social life as a representation of minds and individual and group identity. Language consists of a series of sounds systemized in the form of symbols, and has free, significant, conventional, universal, productive, diverse, dynamic, and humane characteristics. As a communication tool, language allows individuals to interact in social groups, convey messages, and identify themselves in society. In addition, language reflects mental representation, where the form and structure of language follow or mimic minds and ideas. Language is also considered a personality trait that reflects an individual’s beliefs and values. This research aimed to increase understanding of the role of language as a communication tool, mind representation, and identity. The research method involved an in-depth literature review, analysis of linguistic data, and observation of social phenomena in everyday language use. The analysis used a descriptive and interpretive approach to understand the relationship between language, mind, and identity. The results showed that language not only functions as a tool to convey messages but also as a medium that reflects mindset, cultural values, and social identity. The choice of language code was closely related to language ethics, influenced by a community’s social and cultural rules. This research concluded that language was a reflection of human complexity in thinking, communicating, and building identity. Using language in accordance with language ethics contributed to forming a positive image of individuals in society.